Effectiveness of “Isi Piringku” in Pregnant Women with Chronic Energy Deficiency - Endah Purwanti Handayani; Yustika Rahmawati Pratami; Siti Rohmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
This research is a 2024 KEMERDIKBUDRISTEK Grant research which is a development of one form of innovation in accordance with Health Technology Assessment which is able to answer the problems of pregnant women with chronic energy deficiency by providing measuring plates that can be a tool to help mothers every time they are going to eat. Objective to test the effectiveness of the